Antiinflamation Activity Assay of Ethanol Extract of Rhabdastrella sp Sponge Using Denaturation of Chicken Egg Albumin Protein Method - Mahfur Mahfur; Khafid Mahbub; Dina Achada; Ika Vina Dika (Jurnal FARMASIMED (JFM), 2025)
Inflammation is a body defense mechanism by the presence of cell damage against harmful stimuli caused by pathogens, toxic compounds, or irradiation. Drugs that have been used have adverse side effects for the body. The use of natural ingredients is an alternative, one of which is natural ingredients from the sea, namely Rhabdastrella sp. The sponge genus Rhabdastrella has various bioactivities such as anticancer, antimalarial, antibacterial, chemopreventive, anti-inflammatory, antioxidant, cardioprotective, insecticidal, antidiabetic, cytotoxic. Other species of the Genus Rhabdastrella, such as the sponge Rhabdastrella sp. has never been studied. The purpose of this study was to determine the antiinflamation activity of the ethanol extract of the sponge Rhabdastrella sp. The research method was carried out using the method of denaturation of chicken egg protein. The sponge Rhabdastrella sp. was extracted with 96% ethanol. The anti-inflammatory test with protein denaturation used spectrophotometry at a wavelength of 660 nm. concentrations of sample are 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm. The positive control comparison used sodium diclofenac with concentrations are 3.12 ppm; 6.25 ppm; 12.5 ppm; 25 ppm; and 50 ppm. The results showed that the ability to inhibit protein denaturation of 20% ethanol extract of Rhabdastrella sp. was obtained at 70.29 ppm, while the IC50 of the ethanol extract obtained was 280.33 ppm. These results were significantly different from the positive control of sodium diclofenac, which was 36.51 ppm. The anti-inflammatory activity of the sample sponge extract was very small because the content of compounds that have anti-inflammatory abilities, including flavonoids, was only about 2%. Based on this, the sponge extract of Rhabdastrella sp. is not potential as an anti-inflammatory.